Vocal characteristics of prairie dog alarm calls across an urban noise gradient. (6th December 2019) - Shannon, Graeme; McKenna, Megan F; Wilson-Henjum, Grete E; Angeloni, Lisa M; Crooks, Kevin R; Wittemyer, George
Abstract: Increasing anthropogenic noise is having a global impact on wildlife, particularly due to the masking of crucial acoustical communication. However, there have been few studies examining the impacts of noise exposure on communication in free-ranging terrestrial mammals. We studied alarm calls of black-tailed prairie dogs ( Cynomys ludovicianus ) across an urban gradient to explore vocal adjustment relative to different levels of noise exposure. There was no change in the frequency 5%, peak frequency, or duration of the alarm calls across the noise gradient. However, the minimum frequency—a commonly used, yet potentially compromised metric—did indeed show a positive relationship with noise exposure. We suspect this is a result of masking of observable call properties by noise, rather than behavioral adjustment. In addition, the proximity of conspecifics and the distance to the perceived threat (observer) did affect the frequency 5% of alarm calls. These results reveal that prairie dogs do not appear to be adjusting their alarm calls in noisy environments but likely do in relation to their social context and the proximity of a predatory threat. Anthropogenic noise can elicit a range of behavioral and physiological responses across taxa, but elucidating the specific mechanisms driving these responses can be challenging, particularly as these are not necessarily mutually exclusive. Our research sheds light on how prairie dogs appear to respond to noise as a source of increased risk, rather than as a distraction or through acoustical masking as shown in other commonly studied species (e.g., fish, songbirds, marine mammals). Abstract : Songbirds, amphibians, and marine mammals have been shown to alter their vocalizations in noisy environments. We conducted one of the first studies on the effects of noise on communication in a terrestrial mammal—the prairie dog. Interestingly, prairie dogs did not appear to adjust their alarm call frequency or duration with increasing noise exposure, while our previous research demonstrated that their behavioral response to noise is similar to elevated predation risk—reduced foraging and increased vigilance.